The Application of Lesson Study in Improving The Quality of English Teaching - Adieli Laoli; Oskah Dakhi; Maria Magdalena Zagoto (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this study is to analyze the lesson study process in fostering novice lecturers to improve the quality of teaching. This research is qualitative descriptive research by conducting direct observation, interviews, and documentation. The cycle in the lesson study approach consists of 3 main stages: Plan, Do and See. From the results of interviews and documentation conducted at the planning stage of the lesson study, there are several obstacles faced by novice lecturers when teaching the Writing 2 course, including lack of confidence in teaching students, lack of experience, and the use of monotonous methods, media, and poor or inappropriate assessment techniques.